Turbidity Reduction by Using Variations of Filtration Media Sizes (Case Study of Treated Water PT. X Jakarta) - Vembrio, Leonardus Alvin Widi; Zahra, Nurulbaiti Listyendah; Sarwono, Ariyanti; Putri, Natasya Hikmat; Rofiah, Rofiah (Journal of Sustainable Infrastructure, 2023)
Turbidity is one of the main water quality parameters in drinking water quality. One way to reduce turbidity levels is by filtration. The filtration unit in the water treatment plant must use appropriate media so that the processed raw water meets World Health Organization (WHO) standards. WHO states that the turbidity of processed water before disinfection is 1 NTU. This research was conducted to know the efficiency of filtration processing with various media in reducing the concentration of turbidity in raw water. This study used three types of media, namely 50% silica sand with a mesh size of 12-16 and 50% silica sand with a mesh size of 8-12 (C), 100% silica sand with a mesh size of 12-16 (K), and 100% silica sand in mesh size. 8-12 (B). Porosity value for each sample C, K, and B is 0.412; 0.423; and 0.388. The detention time at maximum discharge for samples C, K, and B was 3.6, respectively; 3.76; and 3.45 minutes. The flow rates used for media samples C, K, and B were 4125 L/s and 2500 L/s, respectively. The removal efficiency produced by the highest turbidity was obtained in medium C with values of 90.8% and 89.9%, respectively. Meanwhile, media B gave the lowest turbidity removal efficiency, namely 86.3% and 86.4%. The results of all variations of the media used have met WHO standards, where the processed results have produced turbidity concentrations of 0.25 - 0.32 NTU.